2021
DOI: 10.1177/03635465211028255
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Extra-articular Tenodesis Alters Lateral Compartment Contact Mechanics under Simulated Pivoting Maneuvers: An In Vitro Study

Abstract: Background: There is concern that utilization of lateral extra-articular tenodesis (LET) in conjunction with anterior cruciate ligament (ACL) reconstruction (ACLR) may disturb lateral compartment contact mechanics and contribute to joint degeneration. Hypothesis: ACLR augmented with LET will alter lateral compartment contact mechanics in response to simulated pivoting maneuvers. Study Design: Controlled laboratory study. Methods: Loads simulating a pivot shift were applied to 7 cadaveric knees (4 male; mean ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…However, to date, the advantages of combining LET with ACL reconstruction in pediatric patients have been infrequently evaluated. Moreover, there are some unresolved issues that have been raised in recent studies reporting the theoretical risk of knee overconstraint and the increase in lateral compartment pressures, 23,34,48 which can accelerate degenerative joint changes. It remains unclear whether such findings result in alterations in bone growth in patients who are still developing.…”
mentioning
confidence: 99%
“…However, to date, the advantages of combining LET with ACL reconstruction in pediatric patients have been infrequently evaluated. Moreover, there are some unresolved issues that have been raised in recent studies reporting the theoretical risk of knee overconstraint and the increase in lateral compartment pressures, 23,34,48 which can accelerate degenerative joint changes. It remains unclear whether such findings result in alterations in bone growth in patients who are still developing.…”
mentioning
confidence: 99%
“…In the same study, a clinically performed PS demonstrated an ATT of -10 mm and an ETR of approximately 15 ◦ . Loading profiles from this study were also adopted by other clinical trials [68]. Other studies reported values of -8 up to -12 mm of ATT and 15 ◦ - 21 ◦ of tibia rotation [72].…”
Section: Resultsmentioning
confidence: 99%
“…We would like to assess the impact of LET in future FE simulations that involve boundary conditions from rigid multibody dynamics resembling such activities. For example, the developed lateral tibiofemoral contact pressures after LET or the impact of ITB debilitation to knee loading due to graft harvesting are debatable topics that we would like to address [57, 68, 84, 85]. Moreover, in the scope of this work we developed a loading profile that seems to trigger the desired PS movement for the given knee model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because LET is a non-anatomical reinforcement procedure, the main concern is its potential to over-constrain the lateral compartment, causing stiffness or accelerated development of lateral compartment osteoarthritis (OA). Some biomechanical studies have shown that the addition of LET to ACLR induced the over-restriction of tibial internal rotation compared to the intact knee [16,46]. Specifically, Inderhaug et al, suggested that the constraint on knee kinematics is affected by graft tension and knee flexion angle during fixation.…”
Section: Lateral Extra-articular Tenodesismentioning
confidence: 99%